2016
DOI: 10.1289/ehp.1509824
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Air Pollution and Traffic Noise Exposures and Mild Cognitive Impairment in Older Adults: A Cross-Sectional Analysis of the Heinz Nixdorf Recall Study

Abstract: Background:Mild cognitive impairment (MCI) describes the intermediate state between normal cognitive aging and dementia. Adverse effects of air pollution (AP) on cognitive functions have been proposed, but investigations of simultaneous exposure to noise are scarce.Objectives:We analyzed the cross-sectional associations of long-term exposure to AP and traffic noise with overall MCI and amnestic (aMCI) and nonamnestic (naMCI) MCI.Methods:At the second examination of the population-based Heinz Nixdorf Recall stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 40 publications
(58 reference statements)
3
110
2
3
Order By: Relevance
“…Decreased cognitive and central nervous system function from long-term traffic-related air pollution was also reported in cohort studies in the United States [20,24]. A cross-sectional study in Germany reported a positive association between exposure to traffic-related air pollution and cognitive impairment [21], while weak associations between traffic-related PM 2.5 and decline in memory performance were found in the United Kingdom [25]. Nitrogen oxides, common markers of traffic-related air pollution, were associated with greater incidence of Alzheimer's disease in longitudinal studies in Sweden and China [19,26].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Decreased cognitive and central nervous system function from long-term traffic-related air pollution was also reported in cohort studies in the United States [20,24]. A cross-sectional study in Germany reported a positive association between exposure to traffic-related air pollution and cognitive impairment [21], while weak associations between traffic-related PM 2.5 and decline in memory performance were found in the United Kingdom [25]. Nitrogen oxides, common markers of traffic-related air pollution, were associated with greater incidence of Alzheimer's disease in longitudinal studies in Sweden and China [19,26].…”
Section: Introductionmentioning
confidence: 64%
“…Epidemiological studies have reported associations between road proximity and traffic-related air pollution (e.g. nitrogen dioxide) with impaired cognitive function in adults and incidence of neurological disorders [18][19][20][21]. Two longitudinal studies in Germany reported that shorter residential distance to roads was positively associated with worse cognitive performance [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent follow up study of this population, levels of mono-nitrogen oxides (NO x ) were associated with a decline in a global test score across neuropsychological tests, and specific associations were seen between visuo-spatial abilities and NO 2 , NO x and PM 10 , as well as the Boston Naming Test with NO x (24). Another German cross-sectional cohort study of 50–80 yr olds found that long term exposures to PM 2.5 air pollution showed a positive association with reduced MCI (scores, particularly amnestic MCI components) (25). Levels of black carbon, a measure of traffic-related pollution were associated with lower Mini-Mental State Examination scores in a population of older men from the VA Normative Aging Study (26).…”
Section: Effects Of Air Pollution On Cognitive Functionsmentioning
confidence: 99%
“…In research by Heinz Nixdorf Recall, Tzivian et al in group of 4,086 people aged 50-80 years it has been demonstrated that the dust contamination of PM2.5 and urban noise correlated positively with the appearance of mild cognitive impairment (MCI). Exposure to urban pollution directly influenced the development of neurodegenerative diseases, which in the future may lead to disturbances of a dementia nature [43]. According to the above facts air pollution in prenatal life and in the lives of youth and adults adversely affects the neuropsychological processes and also has an influence on behavioural and mood disorders.…”
Section: Discussionmentioning
confidence: 99%